The effect of volatility persistence on excess returns. Issue 1 (15th November 2016) - Jain, Ajeet; Strobl, Sascha
Abstract: In this paper, we examine the effect of volatility persistence in explaining excess returns in conjunction with established factors. We use an I‐GARCH model to estimate volatility persistence for each company on the NYSE for each year between 1989 and 2014. We find that volatility persistence is significant in explaining excess returns for medium to high turnover portfolios. We also find a similar relationship for portfolios sorted on size. This study tries to disentangle the effects of various information asymmetry aspects in asset pricing and show that not only volatility itself but also its persistence is important in explaining returns.